2020
DOI: 10.1016/j.jcmg.2018.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress-Related Neural Activity Associates With Subclinical Cardiovascular Disease in Psoriasis

Abstract: and received payment for continuing medical education work related to psoriasis that was supported indirectly by Lilly and Ortho Dermatologics. 3.Dr. Tawakol reports grants from Genentech and Actelion for research outside the submitted work. 4.Dr. Powell-Wiley has received funding from the National Institutes of Health Intramural Research Program (ZIA HL006168).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 41 publications
(70 reference statements)
2
51
1
Order By: Relevance
“…Moreover, individual differences in amygdala function have been associated with clinical cardiovascular endpoints, cardiometabolic outcomes that are conducive to atherosclerotic CVD and even surrogate markers of pre-clinical atherosclerosis that are all presaged by autonomic, immune and neuroendocrine dysregulation. Elevated resting metabolic activity of the amygdala, for example, confers risk for cardiovascular events ( Tawakol et al., 2017 ), incident diabetes ( Osborne et al., 2019 ), the progression of visceral adiposity ( Ishai et al., 2019 ) and non-calcified coronary plaque ( Goyal et al., 2018 ). The latter findings build on earlier cross-sectional evidence that pre-clinical atherosclerosis in the carotid arteries associates with elevated metabolic activity in the medial temporal lobe ( Sojkova et al., 2010 ) and—more specifically—with amygdala reactivity to facial expressions of fear and anger ( Gianaros et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, individual differences in amygdala function have been associated with clinical cardiovascular endpoints, cardiometabolic outcomes that are conducive to atherosclerotic CVD and even surrogate markers of pre-clinical atherosclerosis that are all presaged by autonomic, immune and neuroendocrine dysregulation. Elevated resting metabolic activity of the amygdala, for example, confers risk for cardiovascular events ( Tawakol et al., 2017 ), incident diabetes ( Osborne et al., 2019 ), the progression of visceral adiposity ( Ishai et al., 2019 ) and non-calcified coronary plaque ( Goyal et al., 2018 ). The latter findings build on earlier cross-sectional evidence that pre-clinical atherosclerosis in the carotid arteries associates with elevated metabolic activity in the medial temporal lobe ( Sojkova et al., 2010 ) and—more specifically—with amygdala reactivity to facial expressions of fear and anger ( Gianaros et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, psoriasis is associated with a variety of comorbidities including metabolic syndrome, cardiovascular diseases (CVDs), inflammatory bowel diseases, and various other systemic conditions. [2][3][4][5][6][7][8][9][10] C-reactive protein (CRP) is a polypeptide and acute-phase reactant synthesized mainly by the hepatocytes during inflammation in response to certain cytokines, such as interleukin (IL)-1, IL-6, and tumor necrosis factor (TNF)-α. [11][12][13][14] High-sensitivity CRP (hs-CRP) can show small changes in CRP levels during inflammation; therefore, it is a much more sensitive marker than CRP.…”
Section: Introductionmentioning
confidence: 99%
“…Increased amygdalar metabolic activity induced through sympathetic nervous system pathways the activation of the bone marrow and thus boosted the release of inflammatory cells with the consequence of increased vascular inflammation [ 63 ]. The same pathways were elucidated in a sample of patients with psoriasis, a chronic inflammatory skin disease: Increased metabolic activity of the amygdala led to hematopoietic system activation with increased release of activated monocytes stimulating inflammation and atherosclerosis [ 11 ]. Other neuroimaging studies showed that amygdala activity was associated with baseline visceral adiposity as well as an increase in visceral adiposity [ 17 ], and the development of diabetes mellitus independent from adiposity [ 48 ].…”
Section: Amygdala Activation and Inflammationmentioning
confidence: 99%